Forecasting Joule Thief Efficiency Using Fuzzy Logic Method - Jamaaluddin, Jamaaluddin; Akbar, Ilham Yusuf; Hadidjaja, Dwi; ahfas, Ahmad (Journal FORTEI-JEERI, 2025)
The electrical device is initially require energy to operate now gradually began to change with a device that could save electricity and more environmentally friendly,Eifisien is the ratio between the input (input) and output (between benefit with the resources used. Joule Thief has the potential to become an innovation because it is able to generate electrical energy through the development of electrical components that generate electromagnetic fields in coils or coils. Where in this analysis using using fuzzy logic to analyze the efficiency of Joule Thief. Of testing and research that has been downLighted lamps old forecasting for the Joule Thief circuit on the primary winding 10 and secondary winding 17 obtained the value of the average percentage error 0.2994, Then on the primary winding and the secondary winding 5 7 Average values obtained percentage error 0434 as well as on the primary winding 5 and the secondary winding 20 obtained average value percentage error 0.8711, Based on these data also concluded that the Joule Thief with the primary winding 10 and secondary winding 17 is the most efficient because it has an average percentage of a small error is 0.2994.